Characterization of genetic diversity in selected cultivars and identification of a possible molecular marker for drought tolerance in tea Camellia sinensis (L.) O. Kuntze - Apostolides, Zeno (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2009.